Contribuições do pensamento de Paulo Freire para o ensino de biologia - Matsuno, Vania Masami (2021)
This research aimed to seek possible contributions from Freire’s framework to the teaching of biology in order to stimulate the development of students’ critical thinking. For this reason, a literature review on this topic was carried out and guided the theoretical foundation. The theoretical framework had Paulo Freire as main author, complemented with authors whose research focuses on teaching Science, ScienceTechnology-Society-Environment and scientific literacy, namely: Demétrio Delizoicov, José André Angotti, Marta Maria Pernambuco and Antonio Fernando Gouvêa da Silva. At the empirical level, with an approximation of participatory action research, data were collected at a state public school in the east zone of the city of São Paulo, Brazil, aiming to identify, in theory and in practice, the Freirean principles that can guide the teaching of biology. Data production used the following procedures: observation, interview, development of workshops and document analysis. As main results, there are indications for a significant work with students in the teaching of biology, in a criticaltransforming perspective, from Freire’s references and fundamentals to compose a proposal for teacher education